The implications of virtual reality technology in e-commerce - Estifaei, H.; Riza, Mustafa; Manesh, Hamed Farahani (My University, 2010)
The growth of e-commerce in recent years has opened up new trade avenues for enterprises. It is clear that internet websites in this context are playing an important role as the medium of information dissemination. Many studies have been shown that 2-D representations of products are no longer impressive on websites than before, since demands for custom-designed products are rapidly increasing. In the consideration of the industrial equipments, this situation becomes more important since such equipments are costly to buy. Due to advent of high-speed network and advance in computer graphics, the Virtual Reality (VR) technology emerged as alternative way to resolve problems inherent to the conventional methods by improving presentation ability and flexibility for customers. In this paper, typical motivations are presented to highlight why and how e-commerce can benefit from VR applications. Representative VR applications and potentials are presented in the areas of industrial equipment producers. ©2010 IEEE.
IEEE International Conference on Industrial Engineering and Engineering Management, IEEM2010 --
Keywords: E-commerce; Manufacturing equipments; Marketing; Virtual reality